The Role of Women in East Kalimantan's Economic Growth - Purba, Samuel Fery (Puslatbang KDOD Lembaga Administrasi Negara, 2024)
Gender equality is essential because it indicates justice and equality for men and women with the same rights, obligations, and opportunities, resulting in economic growth in the region and country. This study aims to analyze the effects of women's roles: the gender development index (GDI), the gender empowerment index (GEI), the percentage of women as professionals (PWP), the mean years of schooling for women (MYSW), and the women's life expectancy (WLE), on economic growth in East Kalimantan. This study used secondary data from Statistics of East Kalimantan Province (BPS). This data was analyzed using panel data regression covering from 2017 to 2021 from 10 cities/regencies in East Kalimantan. The findings indicate that GEI significantly influences economic growth in East Kalimantan, whereas GDI, PWP, MYSW, and WLE do not significantly affect economic growth. This lack of impact can be attributed to women's limited involvement and participation in various sectors, including economics, education, and health. Consequently, programs aimed at enhancing GDI, PWP, MYSW, and WLE have not translated into tangible economic growth in East Kalimantan. To address this, local governments and stakeholders in East Kalimantan must increase women's participation in political spheres such as parliament and higher education, ensure access to healthcare, and fortify regulations and institutions promoting women's rights, fostering regional economic growth